2011
DOI: 10.1016/j.anbehav.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Moonlight and shelter cause differential seed selection and removal by rodents

Abstract: foraging ecology predation risk Queráis scatter hoarding seed size wood mouse Various environmental factors may influence the foraging behaviour of seed dispersers which could ultimately affect the seed dispersal process. We examined whether moonlight levels and the presence or absence of rodent shelter affect rodent seed removal (rate, handling time and time of removal) and seed selection (size and species) among seven oak species. The presence or absence of safe microhabitats was found to be more important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 51 publications
(63 reference statements)
7
88
1
Order By: Relevance
“…We expected a more rapid seed predation on the ground in agreement with the "reduced finickiness" hypothesis (Leaver & Daly 2003, Perea et al 2011 where animals search for food more rapidly and less selectively in areas with higher levels of predation risk. Our results revealed a slower seed predation on the ground in comparison to the tree only for Chaffinches (the species more accustomed to foraging on the ground of forests; Marler 1956, Kear 1962, Newton 1967, and therefore, an increase in vigilance time on the ground could be a trait favored by selection.…”
Section: Seed Availability In the Treesupporting
confidence: 61%
“…We expected a more rapid seed predation on the ground in agreement with the "reduced finickiness" hypothesis (Leaver & Daly 2003, Perea et al 2011 where animals search for food more rapidly and less selectively in areas with higher levels of predation risk. Our results revealed a slower seed predation on the ground in comparison to the tree only for Chaffinches (the species more accustomed to foraging on the ground of forests; Marler 1956, Kear 1962, Newton 1967, and therefore, an increase in vigilance time on the ground could be a trait favored by selection.…”
Section: Seed Availability In the Treesupporting
confidence: 61%
“…In fact, studies monitoring individual movements have found that home ranges shrink when exposure to predation increases (Tew and Macdonald , Tattersall et al ). Regarding foraging behavior, wood mice invest less effort in food selection and manipulation in risky environments than in safe ones (Perea et al ). In our model, the landscape matrix became more permeable, and consequently dispersal distances increased, when mice perceived lower predation risks or took riskier decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This conditional mutualism depends on a fine balance in which environmental conditions shape rodents’ hoarding activity (Den Ouden et al , Theimer ). Key environmental factors that condition the outcome of the mouse–oak relationship by driving mouse behavior are: 1) intraspecific competition for acorns (defined as the ratio between local mouse abundance and acorn crop),which is related to the net benefits between in situ seed consumption versus hoarding, post‐dispersal acorn retrieval and the likelihood of cache pilferage by conspecifics (Theimer , Vander Wall ) and 2) the presence of shelter, which conditions mouse perception of predation risks while mobilizing seeds (Perea et al , ). Forest fragmentation may have major effects on these factors.…”
mentioning
confidence: 99%